Madness and Creativity: Yes, No or Maybe? - Anna Abraham (Frontiers Research Topics, 2015)
The pervasive idea that madness and creativity are intricately linked is one that holds tremendous fascination for both scientists and the general public alike. Although this view was at first largely driven by anecdotal evidence showcasing the manifestation of mental illness in individuals who exhibited extraordinary levels of creativity in various spheres of life, it initiated a strong impetus to empirically investigate the association between mental health and creativity. A variety of approaches (and combinations of approaches) have been adopted to address this association including clinical, personality, psychometric, behavioral, cognitive, historiometric and neuroscientific. Despite the ever accumulating body of evidence over the past six decades investigating this link, what is lacking is a comprehensive overview of the disparate findings from these different approaches that will enable us to address the question of whether there is an empirically founded relationship between creativity and mental illness. And if such a link does exist, what is the nature of this association? The purpose of this Research Topic was to motivate theorists and researchers to answer this question (or at least attempt to do so) given the available evidence thus far. The themes of interest that were open to exploration in view of this topic included: (a) Which mental disorders are positively associated with creativity? (b) Which mental disorders are negatively associated with creativity? (c) The dynamics of information processing biases (positive versus negative) associated with psychiatric and high-risk populations (d) Theories regarding the madness-creativity link (e) Personality-based studies on creativity (f) Creativity, mental illness and the brain (g) Genes and creativity (h) How can studies on neurological populations inform this debate? (i) What are the areas of impact with regard to real world applications and practice? (j) Historical timeline of this question (k) Evolutionary perspectives on the madness-creativity link (l) Methodological problems associated with this field (m) Philosophical issues to bear in mind when investigating this domain (n) The usefulness of the "troubled genius" concept The invitation to contribute was open to all interested academics regardless of whether they were seasoned explorers within this field of study or just beginning to get their feet wet in its murky waters. As a result of adopting this inclusive approach, the contributions showcase a wide variety of perspectives from academic departments and institutions the world over. What is most encouraging is that so many were willing to openly take on the challenge of tackling this difficult question head on. We hope future discussions that follow through as a result of this collective effort will prove to be just as fruitful.